Design, Synthesis and Biological Evaluation of Potent and Selective S1PR1 Agonists for the Treatment of Ulcerative Colitis. Issue 22 (23rd August 2022) - He, Huan; Xie, Mengting; Zhang, Mengting; Zhang, Haiqin; Zhu, Huan; Fang, Yuxian; Shen, Zihao; Wang, Rui; Zhao, Zhenjiang; Zhu, Lili; Qian, Xuhong; Li, Honglin
Comprehensive Summary: The binding of Sphingosine‐1‐phosphate (S1P) with the S1PR1‐5 plays a fundamental physiological role in a number of processes including vascular development and stabilization, lymphocyte migration and distribution. S1P‐S1PR1 signal axis established roles in immune cell trafficking thus playing a therapeutic role in multiple sclerosis and inflammatory bowel disease. In this study, a series of oxadiazole derivatives were designed and synthesized as S1PR1 agonists based on rational drug design. Among them, compound 9i was identified as a potent and selective S1PR1 agonist with activities on β ‐arrestin recruitment (EC50  = 0.36 nmol/L) and receptor internalization (EC50  = 8.09 nmol/L). Meanwhile, compound 9i displayed an oral bioavailability up to 93.6%. Based on its excellent activity to S1PR1 and pharmacokinetic properties, compound 9i effectively alleviated dextran sulfate sodium (DSS)‐induced ulcerative colitis in mice at a dose of 0.1 mg/kg. Abstract :